Inverse association between uric acid levels and muscle quality index in adults: a cross-sectional analysis of NHANES 2011-2014 - Haibin Wen; Xianhua Li; Ning Tan (BMC, 2024)
Abstract Objective The objective of this study was to delineate the association between serum uric acid (UA) levels and Muscle Quality Index (MQI), assessing muscle strength relative to mass, in adults aged 20 to 59 years. Methods Utilizing data from the National Health and Nutrition Examination Survey (NHANES) 2011-2014, this study examined the association between UA levels and MQI-a ratio of muscle strength to mass. Weighted linear models, adjusted for potential confounders, assessed the relationship, with a generalized additive model (GAM) probing for non-linear patterns. Subgroup analyses and interaction effects were conducted using weighted linear regression across diverse demographic and clinical groups to ensure the robustness and reliability of our findings. Results Among 5,277 participants, a significant inverse association was observed between UA levels and MQI, with a 0.08 decrease in MQI per 1 mg/dL increase in UA (95% CI: -0.11 to -0.06, p < 0.001). The negative trend was dose-dependent across UA quartiles, which was most pronounced in the highest quartile (Q4: -0.28, 95% CI: -0.36 to -0.19, p < 0.001). Curve-fitting analysis revealed a consistent inverse relationship without evidence of non-linearity. Stratified analyses reinforced the core findings across all examined subgroups, highlighting the universal relevance of the observed association. Conclusion Our findings demonstrate a significant inverse association between elevated serum UA levels and MQI, highlighting the potential importance of uric acid management in enhancing muscle quality among young and middle-aged adults. The consistency of this relationship across different subgroups underscores the need for targeted strategies and interventions to manage UA levels. Future research should explore longitudinal impacts and intervention outcomes to further elucidate the potential benefits of uric acid management on muscle health.